Assessment of adaptive walking performance - Lindemann, U.; Klenk, J.; Becker, C.; Moe-Nilssen, R. (Medical engineering & physics, 2013)
Although mostly negative aspects are reported to be associated with gait variability, irregular walking is needed when walking performance has to be adapted to specific environmental conditions. The aim of this study was to evaluate the test–retest reliability and discriminative ability of a measure to assess adaptive walking performance and to identify parameters associated with test performance in young and elderly subjects. Eighteen older (mean age 78.1 years) and 19 young women (mean age 30.8 years) were instructed to walk as precisely as possible over a defined course targeting 26 arbitrarily positioned rectangle boxes fixed on an instrumented walk way with embedded pressure sensors. ICC1,1 of 0.79 demonstrated sufficient reliability in the cohort of older women. Targeting was significantly worse (or deviation was larger) in older women than in young women (mean 3.20cm versus 2.27cm, p=0.005). Mean gait speed of the older women was higher during the test (0.50m/s versus 0.40m/s, p=0.020), but not during unconstrained walking (1.15m/s versus 1.50m/s, p<0.001). The deviation measure classified 78% of the subjects into correct age group (sensitivity 67%, specificity 90%, p=0.003). Adaptive walking performance was associated with parameters describing physical performance as well as with cognitive executive function. This study shows that this test of adaptive walking performance is a reliable measure of irregular walking with ability to discriminate between young and older subjects. Our results suggest that older persons might try to camouflage their lack of accuracy during adaptive walking by higher gait speed.